Numerical investigation of heat transfer and melting process in a PCM capsule: Effects of inner tube position and Stefan number. (October 2021) - Bouzennada, Tarek; Mechighel, Farid; Filali, Abdelkader; Ghachem, Kaouther; Kolsi, Lioua
Abstract: The present paper presents a 2D-symmetric numerical study within a new-suggested configuration of a PCM's capsule aimed to investigate the heat distribution and the melting time under the effect of different factors including the position of the inner-tube and its temperature wall that is presented by Stefan number. This capsule involves an inner-tube allowing a heat transfer fluid (HTF) to flow through it and surrounded by a phase change material PCM (n-Octadecane). The governing equations are solved by using Comsol-Multiphysics commercial code. The results reveal that both heat-transfer/melting rates are improved when the inner-tube moving downward or with increasing the Ste number. whereas with the same Ste value (Ste = 0.06), the melting rate and the stored energy are better by 15.29 % and 25.77 % for the central and bottom position cases respectively than the top position. on other hand the lowest results are found in the case of Ste = 0.06 and when the HTF-tube is located in the top position, besides the case of Ste = 0.15 and when the HTF-tube is located in the bottom position provides the best results by 28 % .